2008
DOI: 10.1590/s1809-29502008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da fisioterapia respiratória sobre a pressão arterial em recém-nascidos pré-termo

Abstract: RESUMO: Oscilações na pressão arterial (PA) sistêmica são diretamente proporcionais às oscilações do fluxo sangüíneo cerebral nos prematuros, mas são escassos os estudos acerca do efeito dos procedimentos fisioterapêuticos sobre a PA. Este estudo investigou a repercussão desses procedimentos e da aspiração endotraqueal na pressão arterial em recém-nascidos pré-termo (RNPT) na primeira semana de vida. Foram estudados 42 RNPT com peso de nascimento menor que 1.500 gramas em ventilação mecânica. A PA foi mensurad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…Low-weight males predominated, with moderate prematurity and ventilation in ambient air in both the groups. Whereas very low weight females predominated in the clinical research reported by Nicolau and Falcão 23 with extreme prematurity and mechanical ventilation that showed that the systemic arterial pressure of 42 PTNB stayed within the physiological values after respiratory physiotherapeutic procedures, different from the present study.…”
Section: Physiotherapycontrasting
confidence: 93%
“…Low-weight males predominated, with moderate prematurity and ventilation in ambient air in both the groups. Whereas very low weight females predominated in the clinical research reported by Nicolau and Falcão 23 with extreme prematurity and mechanical ventilation that showed that the systemic arterial pressure of 42 PTNB stayed within the physiological values after respiratory physiotherapeutic procedures, different from the present study.…”
Section: Physiotherapycontrasting
confidence: 93%
“…The greater understanding of pathophysiological mechanisms involved allowed the development of new therapeutic resources in perinatal care improvement contribution 1 . Associated with mechanical ventilation and allied to traditional forms of drug administration, parenteral and oral, the new concept of topical treatment in respiratory diseases represents a considerable advance, allowing the maximization of therapeutic effects, enabling directly the airways through endotracheal inhalation, with less risk of systemic side effects: it happens using beclomethasone and furosemide [2][3][4] . The glucocorticoids have multiple mechanisms of action and effects, including the inhibition of arachidonic acid metabolism and its action on the inflammatory process inhibiting diapedesis of phagocytic cells, which allows the capacity of lymphocytic cells increase and have more functions 3,5 .…”
Section: Introductionmentioning
confidence: 99%